ALGORITHM FOR CONSTRUCTING ROUTES IN A MOBILE APPLICATION FOR NAVIGATION IN LARGE AREAS OF SERVICE - Моисеенко, Елена (SWorldJournal, 2020)
The article analyzes the algorithms for constructing the shortest path such as Dijkstra’s algorithm, Ford’s algorithm, width search algorithm.The disadvantages of these algorithms for their application in the mobile application for navigation are identif